How COVID-19 has Permanently Changed Consumer Behaviour and the Consequent Developments in the Delivery of Goods and Services - Cassandra Ranee; Rohit Kar (International Journal of Engineering and Management Research, 2022)
As we see the world slowly limping back on its feet and returning to normal, one cannot ignore the change in consumer behaviour in almost all areas specifically in our buying behaviour and consumption pattern of groceries, retail goods, health and healthcare products, travel and tourism, entertainment, dining and food delivery, work and education and learning. These changes in almost all areas of life will have important implications to providers and will help them prepare for the new normal. While there has been a strong shift towards online and digital modes of delivery of almost all products and services it has also been noticed that while it has been seen to be beneficial to certain areas in certain areas outcomes have not been very positive especially in learning, remote work etc. Of course areas such as tourism, aviation, public transportation, suffered tremendously due to the nature of their business. While all these are slowly showing a comeback after the difficult period of two years, consumer behaviour has changed forever post Covid. This paper aims to study the changes in consumer behaviour and will try to determine if these changes will remain. As we know behavioural changes are not permanent and their stickiness will depend on satisfaction of the new experiences and also on the number of people who have access to these new delivery methods.